Joint load balanced stable routing and communication segment assignment in mobile cognitive radio ad‐hoc networks. (30th May 2018) - Amiri‐Doomari, Soodeh; Mirjalily, Ghasem; Abouei, Jamshid
Summary: The fundamental issues in mobile cognitive radio ad‐hoc networks are the selection of the optimal stable paths between nodes and proper assignment of the frequency channels/time slots (communication segments) to the links. In this paper, a joint load balanced stable routing and communication segment assignment algorithm is proposed that considers jointly the mobility prediction, mitigating the co‐channel interference and energy consumption. The novelty of the proposed algorithm lies in the increasing of the path stability, which benefits from the maximum link lifetime parameter and introduced weighting function to keep routes away from the PU's region. This avoids the negative impacts on the PUs' operations and decreases the conflict of the cognitive nodes. In the proposed algorithm, the concept of load balancing is considered that yields in the balancing energy consumption in the network, improving the network performance and distributing traffic loads on all available channels. The effectiveness of the proposed algorithm is verified by evaluating the aggregate interference energy, average end‐to‐end delay, goodput, and the energy usage per packet under 6 scenarios. The results show that the performance of the proposed algorithm is significantly better than the recently proposed joint stable routing and channel assignment protocol. Abstract : In this paper, we propose a joint load balanced stable routing and communication segment assignment algorithm in mobile cognitive radio ad‐hoc networks that considers jointly the mobility prediction, mitigating the co‐channel interference and energy consumption. The effectiveness of the proposed algorithm is verified by evaluating the aggregate interference energy, average end‐to‐end delay, good put, and the energy usage per packet.